Pengaruh Kualitas Pelayanan dan Citra Destinasi terhadap Kepuasan Pengunjung dan Loyalitas Pengunjung Destinasi Pantai Lon-Malang - Jamilatul Hasanah; Pribanus Wantara (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of service quality and destination image on visitor satisfaction and loyalty of visitors to the Lon Malang Beach destination. This research uses a quantitative approach with analytical methods Structural Equation Modeling (SEM), which is processed using a statistical program SmartPLS version 4. The population in this study consisted of tourists who visited Lon Malang Beach, with a sample size of 100 respondents selected randomly. The main instrument used in data collection was a questionnaire prepared using a Likert scale to measure respondents' perceptions of the variables studied. The research results show that service quality has a significant influence on visitor loyalty, making it the main factor that plays an important role in increasing tourist loyalty at Lon Malang Beach. In addition, destination image was found to have a smaller influence on visitor satisfaction and loyalty compared to service quality. Visitor satisfaction has also been proven to be an important variable in building loyalty, meaning satisfied visitors are more likely to return to visit in the future. Thus, this research highlights that service quality is a key factor in creating visitor loyalty, while destination image makes a more limited contribution to visitor satisfaction and loyalty at Lon Malang Beach.